Experimental Gasification of Biomass in an Updraft Gasifier with External Recirculation of Pyrolysis Gases - Adi Surjosatyo; Fajri Vidian; Yulianto Sulistyo Nugroho (Journal of Combustion)
The updraft gasifier is a simple type of reactor for the gasification of biomass that is easy to operate and has high conversion efficiency, although it produces high levels of tar. This study attempts to observe the performance of a modified updraft gasifier. A modified updraft gasifier that recirculates the pyrolysis gases from drying zone back to the combustion zone and gas outlet at reduction zone was used. In this study, the level of pyrolysis gases that returned to the combustion zone was varied, and as well as measurements of gas composition, lower heating value and tar content. The results showed that an increase in the amount of pyrolysis gases that returned to the combustion zone resulted in a decrease in the amount of tar produced. An increase in the amount of recirculated gases tended to increase the concentrations of H2 and CH4 and reduce the concentration of CO with the primary (gasification) air flow held constant. Increasing the primary air flow tended to increase the amount of CO and decrease the amount of H2. The maximum of lower heating value was 4.9 MJ/m3.